2015
DOI: 10.1080/02678292.2015.1086443
|View full text |Cite
|
Sign up to set email alerts
|

Mesophase behaviour of laterally di-fluoro-substituted four-ring compounds

Abstract: Four new groups of the di-fluoro-substituted 4-(2′-(or 3′)-fluoro phenylazo)-2-(or 3-) fluoro phenyl-4″-alkoxyphenylazo benzoates (In-IVn) were prepared and investigated for their mesophase behaviour. An alkoxy group of variable chain length (n = 6, 10 and 14 carbons) is attached to the terminal phenylazo benzoate moiety, and two lateral fluoro substituents are attached individually with different orientations to the other two adjacent rings. The molecular structures of the prepared compounds were confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the addition of lateral Cl atom in supramolecular architectures weakens the side by side cohesion interactions thus enhances a nematic phase for all 1:1 complex. Furthermore, the molecular geometry and size of the lateral substituent impact the mesophase stability and the polarizability of the whole molecule [22,23,66]. It was found that the length of the alkoxy chain, the polarity as well as the position (or orientation) of the lateral group are important factors determining the type and the range of the mesophase.…”
Section: Mesomorphic and Optical Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the addition of lateral Cl atom in supramolecular architectures weakens the side by side cohesion interactions thus enhances a nematic phase for all 1:1 complex. Furthermore, the molecular geometry and size of the lateral substituent impact the mesophase stability and the polarizability of the whole molecule [22,23,66]. It was found that the length of the alkoxy chain, the polarity as well as the position (or orientation) of the lateral group are important factors determining the type and the range of the mesophase.…”
Section: Mesomorphic and Optical Behaviormentioning
confidence: 99%
“…[18,19] An incorporation of lateral groups with different size and polarity widely improves many characteristics of liquid crystalline materials. It could be attributed to the disturbance in the molecular packing that decreases the melting temperature and thermal stability of liquid crystal mesophases [20][21][22][23][24][25][26][27]. Lately, azopyridines have been used in the formation of nano-fiber supramolecular self-assembling and hydrogen/halogen-bonding LCs with photo-induced transition phenomena [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The attachment of heterocyclic moiety in the mesomorphic compounds strongly affects polarity and/or polarizability, as well as the geometric arrangement. In addition, the molecular size and shape of the lateral group affects the mesophase stability and the polarizability [45,46]. chain length (n), thus the stability of the N phase is affected by the length of alkoxy chain.…”
Section: Mesomorphic Studies Of 1:2 Hbsmcs A/2bnmentioning
confidence: 99%
“…It could be attributed to the disturbance in the molecular packing that decreases the melting temperature and thermal stability of liquid crystal mesophases. [17][18][19][20][21][22][23][24]. Lately, azopyridines have been used in the formation of nano fiber supramolecular self-assembling and hydrogen/halogen-bonding LCs with photo induced transition phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…From the present investigation, it would be expected that, the increment in the molecular anisotropy due to the orientation of the lateral electron-withdrawing Cl atom in the supramolecular geometry impacted the stability of nematic phase that agrees with our previous work[31,61].Furthermore, the addition of lateral Cl atom in supramolecular architectures weakens the side by side cohesion interactions thus enhances a nematic phase for all 1:1 complexes. In addition, the molecular geometry and size of the lateral substituent impact the mesophase stability and the polarizability of whole molecule[19,20,62]. It found that the length of the alkoxy chain, the polarityas well as the position (or orientation) of the lateral group are importance factors in determining the types and the range of the stability of the mesophase.…”
mentioning
confidence: 99%